Effect of the doping time of the 1‐butyl‐3‐methylimidazolium ionic liquid cation on the Nafion membrane proprieties. (29th May 2018) - da Trindade, Letícia G.; Zanchet, Letícia; Borba, Katiúscia M.N.; Souza, Josiane C.; Leite, Edson R.; Martini, Emilse M.A.
Summary: Nafion membranes were prepared by incorporating in the polymer matrix the 1‐butyl‐3‐methylimidazolium (BMI + ) ionic liquid cation at different doping levels. Increasing the doping time of the membranes with the ionic liquid results in increased incorporation of the BMI + cation but a decrease in the bulk conductivity. The thermogravimetric analysis shows that the BMI + cation incorporation increases the thermal stability of the membranes. The higher discharge efficiency of the fuel cell at 80°C was obtained by using Nafion membrane after 15 minutes of doping in the ionic liquid solution. Abstract : Study on the impact of doping time with ionic liquid on properties of Nafion membrane. The doping of the Nafion membrane with BMI.BF4 ionic liquid improves the thermal stability and the conductivity of the membrane. Improvements on the fuel cell performance by ionic liquid doping are discussed.